Analysis Of Exclusive Rights And Legal Protection For Copyright Owners Of Films Broadcast Through Live Tiktok - Nur Ajeng Sulistiani; Pan Lindawaty Suherman Sewu (Innovative: Journal Of Social Science Research, 2023)
Nowadays many people use the live broadcast application on Tiktok to show movies illegally without regard to moral rights and economic rights for copyright owners, as well as legal protection. This study uses a normative juridical approach method and a conceptual approach. the results of this study show that understanding copyright is important in the entertainment industry in Indonesia. Law No. 28 of 2014 on Copyright (UUHC) explains copyright protection, including the economic rights and moral rights of the creator. Moral rights include the right to be recognized as the creator, the right to state one's name, the right to prevent harmful changes, and the right to withdraw the work. In addition, economic rights give the copyright owner the right to obtain economic benefits from the work. Unauthorized viewing of movies on TikTok constitutes copyright infringement. The copyright owner can take legal steps, such as civil and criminal lawsuits, and report to the Directorate General of Intellectual Property. In addition, TikTok also has rules to fight copyright infringement by blocking infringing users through other user reports.